Immunotherapeutic efficacy of recombinant canine IL-15 as an adjunct to chemotherapy in canine lymphoma - Kang, Min-Hee; Lee, Jaeil; Kim, Sang-Ki; Koh, Kyeyoung; Kang, Mi-Ae; Park, Hee-Myung (Frontiers in Veterinary Science, 2025)
IntroductionCanine lymphoma is a common hematopoietic malignancy with variable response to standard chemotherapy. Interleukin-15 (IL-15) is known to enhance cytotoxic lymphocyte activity, and this study aimed to evaluate the efficacy and safety of a recombinant canine IL-15 (rcIL-15) as an adjunct to chemotherapy in dogs with lymphoma.MethodsA total of 61 dogs diagnosed with lymphoma were enrolled in a 12-week clinical study. The test group received rcIL-15 in combination with standard chemotherapy, while the control group received chemotherapy alone. Outcome measures included tumor response rates, tumor biomarker levels (TK-1, LDH, β2-microglobulin), quality of life (QOL) assessments, and adverse event monitoring.ResultsOf the 61 dogs enrolled, 37 completed the study. The test group demonstrated a higher overall response rate (complete + partial response: 77.8%) compared to the control group (57.9%). Disease progression was observed in 16.7% of dogs in the test group versus 31.6% in controls. Tumor biomarkers were significantly reduced in the test group: TK-1 at 8 weeks (p < 0.0001), LDH at 12 weeks (p = 0.005), and β2-microglobulin at both 8 and 12 weeks (p < 0.05). IFN-γ levels remained stable. QOL parameters, including appetite, activity, and happiness, showed significant improvement. Adverse events were mild, mostly gastrointestinal, and manageable.DiscussionAdjunctive rcIL-15 therapy improved tumor response, reduced biomarker levels, and enhanced QOL with an acceptable safety profile. These findings support the potential of rcIL-15 as a safe and effective immunotherapeutic adjunct for canine lymphoma, meriting further investigation in larger-scale trials.